Edible oil structuring : concepts, methods, and application - Patel, Ashok R. (Food Chemistry, Function and Analysis, 2018)
Driven both by real industrial needs and curiosity for fundamental research, edible oil structuring has emerged as a subject of growing interest to students, academics and scientists involved in the research of this field.